Entrepreneurial university development through the lens of stakeholders. Why? What? and How? - Raihan Taqui Syed; David Spicer (Journal of Innovation and Entrepreneurship)
Abstract The study, with the aim of comprehending the motives and subtleties of developing an entrepreneurial higher education institution (HEI) in Oman, is of significant importance. It explores the interplay among the influencing factors—environmental, organizational, and individual. The findings, which were derived from 36 in-depth, semi-structured interviews involving representatives from key stakeholder groups of an HEI, including prominent external stakeholders such as a government official holding a cabinet rank position and internal stakeholders such as the non-teaching/support staff of the HEI, whose perspectives are often overlooked, shed light on the transformative potential of the ‘Triple Helix Model’ in the entrepreneurial transformation of the HEI. These findings were derived by carrying out thematic analysis using NVIVO software. The research findings illuminate the transformative potential of the ‘Triple Helix Model’ in the entrepreneurial transformation of the HEI. This model, a collaborative effort where the HEI, Government, and Industry work together to create the necessary capital for entrepreneurial development, underscores the importance of organizational leadership. The proactive efforts of the leadership in fostering strong relationships with the other two components drive the entrepreneurial transformation of the HEI, emphasizing the crucial role of each stakeholder in the process. The empirical novelty of this study is threefold: (1) the focus on ‘developing’ an entrepreneurial university, rather than estimating its impact; (2) the incorporation of empirical weight to the knowledge domain of entrepreneurial university through organizational change management concept; and (3) an empirical contribution by applying stakeholder analysis through case study approach. Moreover, the research findings will aid policymakers / governmental agencies in drafting a robust framework for developing entrepreneurial HEIs. This, in turn, would result in producing effective job creators rather than only job seekers, thus alleviating the issue of unemployment and enhancing the pace of societal development.